A prática docente na educação a distância : uma análise segundo a natureza do conhecimento científico - Debastiani Neto, João (2017)
The author Piaget in his study of the construction of scientific knowledge advocate that the knowledge has a three distinct natures, of that the particularities can be observed of the according of the interaction that have in the bloke and the thing. The mathematical-logic knowledge is that on do not find the thing but that on is supported in the things originating thereby in the coordination of the actions of the bloke; Now the physical knowledge that wich is allows cognize the physical particularities of the things, such as colors and proportion; and the social knowledge refers about the convection aspect or subjects of the a certain phenomenon. In consider the specificities of the kind of knowledge in the pedagogic hillside can be observes any misconception wich is a manner of the approached the purport of the distinct theme. The according of any assumptions of the Genetic Epistemology each theme should contemplate the particularities of the knowledge in its area; do not care of the rules of the different fields. Have not any sense teach themes like the Biologic ants Math of the analogous manners, because the first of them need of the useful portion practical, and the second do not can be show solely with contextualization without the logic-deductive arguments. However when consider the distance learning, the new entourage of the teaching-learning is created, bring on reforms in the didactics interactions, primarily regarding at breadths-temporal ranges amongst students and teachers. As a result of the particularities of this type of training, if it presupposes that happens variances both a regards of the instructor experience how much in the way as the purport is introduce, if the in person teach be reference. Still, are these changes of the kind practice influence in the manner of the purport being approached of the teacher? In other words, the teachers who act in distance learning regard the different kind of the knowledge for the ready their classes? Or do they create similar approach with the traditional tuition? And even more, do the changes in the teacher's practice when acting in the distance education intervene in his / her performance in traditional tuition? With inquiries of this mass this thesis was organize, objectifying recognize by means of video lessons, web conferences, courseware and semi-structured interviews analysis, if the teachers consider the different kinds of knowledge when instruct their students in this kind of education. Therefore of this goal be closely connected with the analyses of the purport of video lessons of teachers, of courseware available in the theme in the modality distance learning and the interviews that be performed with the same professionals, it was adopted of methodological procedure the method of Content Analysis based in Bardin (1977). It was possible to understand with this thesis that whilst the physics teachers do not show teaching practices that take in consideration the kind of the knowledge of their scientific area, the teachers of Biology do it considering in parts the epistemological being of the knowledge of this area. In opposition of the physics teacher there are the teachers of History, once they are the ones who come closest to considering the epistemological quality of their area when they minister the subjects .